2017
DOI: 10.4018/ijkbo.2017070102
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Knowledge Management Processes in ERP Implementation Success

Abstract: Due to response to the business goals, organizations need to implement enterprise resource planning systems. But the risk of failure in the implementation project of these systems is so high, therefore paying close attention to the effective factors of implementation is very necessary. One of the effective factors is knowledge management (KM). In this study, the role of Knowledge management processes in implementation of enterprise resource planning systems is studied and the existence of knowledge management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Enterprise value-adding processes Shaqrah and Al Maliki (2018) concluded that enterprise systems implementation area complex process, particularly when using new knowledge through the implementation phase. Batada and Rahman (2012), Rouhani et al (2017) measured ENTVA by using a balanced scorecard model focusing on the internal business process and highlighting the operational efficiency of business processes in enterprises. Azhdari et al (2012) emphasized attaining ENTVA systems by maintaining a knowledge mechanism through standardization, formalization and specialization commitment.…”
Section: Vjikms 531mentioning
confidence: 99%
See 2 more Smart Citations
“…Enterprise value-adding processes Shaqrah and Al Maliki (2018) concluded that enterprise systems implementation area complex process, particularly when using new knowledge through the implementation phase. Batada and Rahman (2012), Rouhani et al (2017) measured ENTVA by using a balanced scorecard model focusing on the internal business process and highlighting the operational efficiency of business processes in enterprises. Azhdari et al (2012) emphasized attaining ENTVA systems by maintaining a knowledge mechanism through standardization, formalization and specialization commitment.…”
Section: Vjikms 531mentioning
confidence: 99%
“…KMSHA is defined as interacting and exchanging employees’ knowledge, experiences and skills socially. This perspective refers to the knowledge exchange between individuals or groups to explicit sources and from a group to the organization (Rouhani et al , 2017). Many obstacles faced organizations in this process.…”
Section: Literature Hypotheses and The Research Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have primarily concentrated on knowledge management. Reference [19] proposed that KM has a positive effect on the successful execution of an ERP system implementation in an organization. Greater knowledge flows can provide significant benefits to the refinement of organizations' inventions early in development.…”
Section: Literature Reviewmentioning
confidence: 99%